Implementation of an Early Mobility Pathway in Neurointensive Care Unit Patients With External Ventricular Devices. Issue 2 (April 2017) - Moyer, Megan; Young, Bethany; Wilensky, Eileen Maloney; Borst, Joseph; Pino, William; Hart, Marisa; LoBreglio, Jesse; Zaleski, Derek; Leonor, Isaira; Kung, David; Smith, Michelle; Zager, Eric; et al.
Abstract : ABSTRACT: Background: Patients with an external ventricular drain (EVD) may not be readily mobilized because of concerns of catheter dislodgment and/or inappropriate cerebrospinal fluid drainage. Delayed mobilization may result in longer hospital stays and an increased risk for complications related to immobility. We aimed to determine the safety, feasibility, and outcome of an EVD mobilization protocol in patients with subarachnoid hemorrhage (SAH).Methods: A multidisciplinary group developed a formal algorithm for the mobilization of patients with SAH with EVDs. Outcome measures included intensive care unit (ICU) length of stay (LOS), day to first mobilization, and discharge disposition. Patients were prospectively enrolled during a 12-month period and compared with a historical control group of patients with SAH for the preceding 12-month period.Results: Thirty-nine of 45 (86.7%) patients were women. Mean age did not differ significantly between the preintervention (n = 19) and postintervention (n = 26) groups (59.6 vs 55.7). Number of EVD device days did not differ significantly between groups (16.3 vs 15, P = .422]. Of 101 attempted postintervention mobilization sessions, six were aborted for increased lethargy (1), pain (1), elevated intracranial pressure (1), drain malfunction (1), and hypotension (2). Twenty-four sessions were attempted but never initiated because of worsening neurologic examination (10), pulmonary instability (2), hemodynamic instability (2), medical instability (3), and provider request (1). No patient experienced catheter dislodgment. Mean ICU LOS was not different between groups (20.7 vs 18.2, P = .262). The day of first mobilization was significantly earlier in the postintervention group (18.7 vs 6.5, P < .0001). The percentage of patients discharged home or to acute rehabilitation was higher in the postintervention group (63.2% vs 88.5%, P = .018], when accounting for Hunt and Hess grade.Conclusions: The mobilization of patients with EVDs is safe and feasible; it may be associated with earlier mobilization, reduced ICU LOS, and better discharge disposition. No major complications were attributable to early mobilization.